Call of duty: Designated market maker participation in call auctions - Erik Theissen; Christian Westheide (University of Cologne, Centre for Financial Research (CFR), 2019)
Many equity markets combine continuous trading and call auctions. Oftentimes designated market makers (DMMs) supply additional liquidity. Whereas prior research has focused on their role in continuous trading, we provide a detailed analysis of their activity in call auctions. Using data from Germany's Xetra system, we find that DMMs are most active when they can provide the greatest benefits to the market, i.e., in relatively illiquid stocks and at times of elevated volatility. They stabilize prices and trade profitably.
Keywords: G10; 330; Designated market makers; Call auctions